Examination of Correlation between Histidine, Sulfur, Cadmium, and Cobalt Absorption by Morus L., Robinia pseudoacacia L., and Populus nigra L. - Ozen, Sukran Akkus; Yaman, Mehmet (Taylor & Francis Inc, 2017)
We investigated the relationship between histidine, sulfur (S), cadmium (Cd), and cobalt (Co) in three hyperaccumulating plants, namely Morus L., Robinia pseudoacacia L., and Populus nigra L. The samples were collected around Gaziantep and Bursa cities because these two cities have more than 1,500,000 populations, in Turkey, as well as they are highly industrialized. Analyses for Cd, Co, and S were done by inductively coupled plasma mass spectrometer (ICP-MS) and for histidine by high-performance liquid chromatography-mass spectrometer (HPLC-MS). Related with role of histidine in detoxification, it was considered that histidine did not bind nickel (Ni) directly in the cytoplasm, but in transport vesicles because metal-rich vesicles had been observed in the cytoplasm of cells of hyperaccumulator plants. The linear correlations were r(his-Cd)=0.70 and r(his-Co)=0.74 for P. nigra L., r(his-Co)=0.52 and r(Co-S)=0.76 for R. pseudoacacia L. It was concluded that P. nigra L. leaves can be considered as hyperaccumulators.
Keywords: Hyperaccumulator plants; ICP-MS; phytoextraction; pollution; trace elements